Uji Efektivitas Ekstrak Etanol Jantung Pisang Kepok (Musa X Paradisiaca L.) sebagai Larvasida Aedes Aegypti - Suwandayani, Muhammad Ali Shodiqin; Marcellia, Selvi; Saputri, Gusti Ayu Rai (Faculty of Medicine and Health Science, Universitas Islam Negeri Maulana Malik Ibrahim, 2023)
Kepok banana heart contains secondary metabolites that have the potential as larvicides. Secondary metabolite compounds that have the potential as larvicides are alkaloids, phenols, flavonoids, saponins, tannins, steroids, and terpenoids. The purpose of this study was to determine whether the ethanolic extract of the kepok banana heart [A1] (Musa x paradisiaca L.) was effective in controlling the Aedes aegypti vector and to determine the LC50 value of the ethanolic extract of the kepok banana heart [A2] which was effective as Aedes aegypti larvicide. The method of extraction of banana buds by the percolation method using 96% ethanol solvent and testing the effectiveness of the larvacide of the kepok banana heart extract as the larvacide of Aedes aegypti. The results of the extraction of the Kepok banana heart as much as 50.5 grams with a yield of 10.1% The results of the Shapiro-Wilk normality test proved that the data were normally distributed with p0.05. Mortality which is effective in killing Aedes aegypti larvae starts at a concentration of 4% with a mortality of 96%. The results of probit analysis obtained an LC50 value of 2.102% so it can be said that the ethanol extract of the kepok banana heart[A3] (Musa x paradisiaca L.) has effectiveness as a larvicide and has toxic properties in killing Aedes aegypti larvae.Keywords: Kepok Banana Heart Extract, Aedes aegypti, Larvicide.